VD_FINDINFO Pron / 2015 / 36 vom 29. Oktober 2015 - VD Tribunal cantonal (2015)
ORDONNANCE, INDEMNITÉEN GÉNÉRAL, ASSISTANCE JUDICIAIRE, RÉDUCTIONEN GÉNÉRAL | 104 al. 3 CPC (CH), 107 al. 1 let. e CPC (CH), 242 CPC (CH), 43 al. 1 let. d CDPJ